PENDAMPINGAN PENENTUAN HARGA POKOK PRODUKSI PADA HOME INDUSTRY SUMBER AGUNG DI PETORAN JEBRES SURAKARTA - Suprihatmi SW; Retno Susanti; Oktavia Darmastuti (Adi Widya : Jurnal Pengabdian Masyarakat, 2022)
tempe chips are the product of Sumber Agung Home Industry. This business is a hereditary effort in order to strengthen the family economy. Tempe chips are a product that is liked by the community, besides being delicious, nutritious, affordable prices are also easy to obtain. This housing business is widely cultivated, in addition to materials that are around the business location, the production process is relatively simple, the capital is not large, the market share is wide open. So it is not surprising that in the development of the Sumber Agung Home Industry, it faces competition, especially in product marketing. This is because in determining the selling price of Sumber Agung, it should be based on the cost of production which is calculated accurately. This has not been able to be done. So far, Sumber Agung has not carried out the process of making the cost of production in business. The FE Unisri Service Team tries to provide assistance in making production prices so that Sumber Agung can set an accurate selling price so that they can compete in selling products. With the determination of the cost of production, Sumber Agung can always develop real expenditures from its production costs in the form of: raw material costs, auxiliary materials, labor costs and factory overhead costs.